Complete mitochondrial genome of an Asian Lesser White-toothed Shrew, Crocidura shantungensis (Soricidae). (June 2013) - Kim, Hye Ri; Park, Joong-Ki; Cho, Jae Youl; Chul Park, Yung
<x xml:space="preserve">Abstract</x> The complete mitochondrial genome was sequenced and annotated newly from an individual of Crocidura shantungensis (Soricidae) from Korea. The total length of the C. shantungensis genome is 17, 160 bp, with a base composition of 32.5% A, 32.7% T, 21.6% C, and 13.1% G.